Effect of smoking cessation on sexual functions in men aged 30 to 60 years - Sahin,Mehmet Oguz (2020)
ABSTRACT Purpose We aimed to evaluate the effects of smoking cessation on the sexual functions in men aged 30 to 60 years. Materials and Methods Male patients aged 30 to 60 years that presented to the smoking cessation polyclinic between July 2017 and December 2018 were prospectively included in the study. The amount of exposure to tobacco was evaluated in pack-year. The patients filled the International Index of Erectile Function (IIEF) form before the cessation and six months after cessation of smoking. Patients were subgrouped according to age, education level and packs/year of smoking and this groups were compared in terms of IIEF total and all of the IIEF domains. Results The evaluations performed by grouping the patients according to age (30-39, 40-49 and 50-60 years) and education level (primary-middle school and high school-university) revealed that the total IIEF scores obtained after smoking cessation were significantly higher compared to the baseline scores in all groups (p=0.007 for the 30-39 years group and p <0.001 for the remaining groups). According to grouping by exposure to smoking (≤25, 26-50, 51-75, 76-100 and 101≥ packs/year), the total IIEF scores significantly increased after smoking cessation in all groups except 101≥ packs/year (p=0.051 for the 101≥ group and p <0.001 for the remaining groups). Conclusions Erectile function is directly proportional to the degree of exposure to smoking, and quitting smoking improves male sexual function in all age groups between 30-60 years of age regardless of pack-year and education level.